PENERAPAN PEMBELAJARAN DENGAN MODEL INDUKTIF MENGGUNAKAN ALAT PERAGA PETAK PINTAR PADA MATERI BILANGAN BULAT DI KELAS VII MTs. TANWIRUL QULUB SUNGELEBAK KARANGGENENG LAMONGAN - Faridah, Luluk; Suwarsono, Muhammad (Universitas Islam Darul Ulum, 2016)
The background of the research was because of the many problems faced by educators and prospective educators about how to study mathematics that favored by learners in accordance with the objectives to be achieved. Therefore we need a suitable model, in addition to the characteristics in accordance with the rules of mathematics and the learning process. Thus, the abstract of math concepts will be easier to understand. While the new concept will settle and attachedÂ to a strong and difficult to remove, so the mathematics achievement of students will be better. The purpose of this study was to determine the level of the effectiveness of inductive learning model application using props clever plot on the integers material in terms of the studentsâ activities, teacherâs activity, studentsâ responses, the completeness of studentsâ learning in class VII MTs. Tanwirul Qulub Sungelebak Karanggeneng Lamongan in the academic school of 2014/2015. The data collection techniques used were observations, questionnaires and tests. Observation method was used to determine the activities of students and teachers during the learning process. The questionnaire method was used to determine the students response to learning that has been done. While the test was used to determine the ability of studentsâ performance and mastery learning both individually and classical. Based on the results obtained during three meetings of the description and analysis of the data as follows: (1) The students thoroughly studied individually with a score of â¥ 75 mastery learning students 25 students out of 28 students, whereas in classical learning completeness obtained a score of 89.28% , (2) The percentage of active student activity by 86.07% and 13.93% of students passive activity. (3) The percentage of active events teachers by 82.14% and 17.86% of teachers passive activity. (4) The percentage of positive responses of students by 93.93% and 6.07% negative responses students. Therefore with the results of this research could be taken into consideration by all educators to try to apply the model of inductive learning by using props clever plot.